Design and Build an Expert System to Discover Children’s Talent with Implementation of Rete Algorithm - Widyanto, Muhammad Arief; Octavany, Octavany; Anthony, Anthony; Indiarto, Bagus (IJTB (International Journal of Technology And Business), 2019)
Many parents are not aware about their children talent. So, their children can?t excel based on their talent. To know their talent, they usually consult with the psychologist by doing talent test. This paper will help the parent to discover their children talent based on USOE standard by build an expert system with implementation of Rete Algorithm. This expert system is built on web based with Django Framework and Python programming language. We use Rete Algorithm because in the previous research, Rete Algorithm can improve the accuracy and give the efficiency by doing the matching process of facts.   Keywords : Child?s Talent, Expert System, Rete Algorithm, USOE Standard